The Role of Language and Literature Pedagogy in Humanistic Education. - Dangku, Yohanes Mariano (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Crisis of values is now taking place in all aspects of life including education. The question to be critically discussed is howdoes language center empower language and literature pedagogy to encounter crisis of values? Languageand literature pedagogy can incorporate ethical values in teaching-learning process. Hence, languageteachers can empower language for learning and forming learners’ personality.Keywords: crisis of ethical values, language pegagogy, literary pedagogy